Congratulations! You are severely underweight—Exploring negative consequences of persuasive system design - Harr, Rikard; Öhlund, Linnea (Frontiers in Computer Science, 2023)
Personal health and wellbeing have grown as an object of study within HCI research and many individuals undergoing weight loss journeys use persuasive systems, such as weight loss apps, to guide them. These systems rely on various principles to persuade users toward their health goal and have in much research been considered having positive effects. There are however also parallel findings indicating unwanted effects. To explore the effects of persuasive system design, we conduct a longitudinal exploratory expert evaluation of 10 free weight loss tracking apps by emulating drastic weight loss for an extended period of time. The objective of the exploration is to unravel potential negative effects of using such systems. Our findings highlight risks of negative effects as some apps take a passive stance toward drastic weight loss, while others actively encourage it through design. We contribute to a growing strand of health related HCI research by mapping out the relation between design and negative consequences of persuasive system use.